CXCL12 promotes CCR7 ligand-mediated breast cancer cell invasion and migration toward lymphatic vessels - Hayasaka Haruko; Yoshida Junichi; Kuroda Yasutaka; Nishiguchi Akihiro; Matsusaki Michiya; Kishimoto Kei; Nishimura Hitoshi; Okada Mari; Shimomura Yuki; Kobayashi Daichi; Shimazu Yoshihito; Taya Yuji; et al. (Wiley, 2022)
Chemokines are a family of cytokines that mediate leukocyte trafficking and are involved in tumor cell migration, growth, and progression. Although there is emerging evidence that multiple chemokines are expressed in tumor tissues and that each chemokine induces receptor-mediated signaling, their collaboration to regulate tumor invasion and lymph node metastasis has not been fully elucidated. In this study, we examined the effect of CXCL12 on the CCR7-dependent signaling in MDA-MB-231 human breast cancer cells to determine the role of CXCL12 and CCR7 ligand chemokines in breast cancer metastasis to lymph nodes. CXCL12 enhanced the CCR7-dependent in vitro chemotaxis and cell invasion into collagen gels at suboptimal concentrations of CCL21. CXCL12 promoted CCR7 homodimer formation, ligand binding, CCR7 accumulation into membrane ruffles, and cell response at lower concentrations of CCL19. Immunohistochemistry of MDA-MB-231-derived xenograft tumors revealed that CXCL12 is primarily located in the pericellular matrix surrounding tumor cells, whereas the CCR7 ligand, CCL21, mainly associates with LYVE-1(+) intratumoral and peritumoral lymphatic vessels. In the three-dimensional tumor invasion model with lymph networks, CXCL12 stimulation facilitates breast cancer cell migration to CCL21-reconstituted lymphatic networks. These results indicate that CXCL12/CXCR4 signaling promotes breast cancer cell migration and invasion toward CCR7 ligand-expressing intratumoral lymphatic vessels and supports CCR7 signaling associated with lymph node metastasis.